Molecular detection of respiratory viruses among Kelantanese hajj pilgrims - Zainuddin , Nur Adlina (2017)
Hajj is a big Muslim gathering that occurs annually, where the Muslims perform several rituals to complete their pillars of faith. According to previous studies, respiratory symptoms were prevalent among Kelantanese hajj pilgrims.Thus, this study was conducted to determine the causes of the viral symptoms among these pilgrims. Specimens were taken in the form of sputum or throat swab after verbal consent was acquired from the Kelantanese pilgrims returning from Hajj from Kuala Lumpur to Kelantan between October 2013 to December 2013. After the sputum specimens were collected in 60mL sterile containers, the swabs were immersed in universal transport media and promptly taken back to the laboratory in USM Kubang Kerian, Kelantan to be stored at -70°C freezer. They were then extracted using a Viral RNA Mini Kit (Qiagen, Germany) and processed using the nested PCR and real-time PCR methods as singleplex reactions. The viruses that were tested include influenza A (FluA), respiratory syncytial virus A (RSVA), respiratory syncytial virus B (RSVB), and human rhinovirus (hRV).The findings and clinical data were analysed in SPSS using t-test for age and Chi-square for the determination of the association of influenza vaccination with their clinical presentation and the association of viral detection among Kelantanese hajj pilgrims with their symptoms and risk factors. In this study, no FluA was detected, whereas RSVA was detected in 40 pilgrims (20.62%). RSVB was detected in 40 pilgrims (20.62%) and rhinovirus was detected in three pilgrims (1.52%). There was no association between FluA vaccination with the clinical presentation of the Kelantanese hajj pilgrims. There was also no association between the detection of virus among Kelantanese hajj pilgrims with their clinical presentation. In addition, there was no association between FluA and RSVA detection among Kelantanese hajj pilgrims with their risk factors. Finally, diabetes mellitus was associated with RSVB detection (p-value=0.049). In conclusion, RSV was the most frequently detected respiratory virus among the Kelantanese hajj pilgrims and RSVB infection had association with diabetes mellitus.